The Putin Phenomenon - White, Stephen; Mcallister, Ian (The journal of communist studies and transition politics, 2008)
The Putin presidency in Russia became increasingly popular as it progressed and a leadership cult developed around the president himself. Not only was there general satisfaction with the leadership as a whole, there was also evidence that it was regarded as increasingly successful in all fields of policy, particularly in international affairs; and focus group discussions as well as surveys suggested the newly elected president, Dmitri Medvedev, would be expected to continue those policies. A closer examination of the survey evidence suggests that the Putin leadership in fact had relatively weak roots in the wider society, and drew widely but superficially on public support. More than anything else it was the strong economic performance of these years that generated support for the Putin presidency, and this suggested that any future leader would depend for his position on maintaining that economic performance in what were now more difficult circumstances.